(untitled) (International Journal of Physiotherapy, 2018)
Background: Nonspecific neck pain is a frequent cause for adults to consult health care providers. Therefore, the physical therapist should always seek the most effective intervention(s) within the wide spectrum of treatments available, so this study was conducted to examine the effect of transcranial laser on somatosensory integration in nonspecific neck pain patients. Methods: Thirty-two male subjects suffering from non-specific neck pain participated in the current study. They were randomly assigned via a balanced stratified assignment. The experimental group (N=16) received trans-cranial infra-red laser (50mw, 90 snm pulsed mode, and 1.2 J/cm 2) over sensory cortex whereas, the control group (N=16) received placebo laser. The assessment of N30 and P22-N30 components of somatosensory evoked potentials (SEPs) were done before and immediately after treatment session for both groups. Results: There was a statistically significant difference between groups regarding N30 peak of SEPs after a single trans-cranial laser session (p=0.0062) with no significant difference between pre and post-treatment data in the experimental group (p=0.0803) and control group (p=0.5577) with a percentage of change (-2.38%) and (1.009%) respectively. In addition, post-treatment results revealed no statistically significant difference between groups regarding an a P22-N30 component of SEPs (p=0.0933). Conclusion: According to the parameters used in the study, it was concluded that trans-cranial laser did not affect somatosensory integration in nonspecific neck pain patients.